Data Acquisition System for Automatic Gear-box of Vehicle Based on xPCTarget - WEI Wei; ZHAO Yong; LI Hong-ren; CONG Da-cheng; HAN Jun-wei (Gong-kuang zidonghua, 2010)
In view of the problem that non-real-time data acquisition system of automatic gear-box of vehicle cannot really reproduce the data during shifting, the paper proposed a design scheme of data acquisition system for automatic gear-box of vehicle based on xPCTarget, and introduced hardware and software of the system in details. The system is built by upper-lower computer to collect data. The upper computer uses visualized graph interface and is operated easily. The lower computer uses a real-time operation system based on xPCTarget, which can collect 26 signals of the automtic gear-box of vehicle including solenoid valve current, temperature, velocity and pressure with 2 ms sampling time, so as to meet analysis requirements well and ensure real-time performance during shifting.